Analysing the Benefits of the Team-of-Teams Model in the Changing Work Environment at the Centre for English Excellence - Teguh Hidayat, Steven; Franksiska, Rosaly (KnE Social Sciences, 2022)
In the current era, volatility, uncertainty, complexity, and ambiguity (VUCA) are common challenges that organizations face. To overcome these challenges, organizations need to develop a flexible organizational structure, one that offers flexibility and adaptability. This research aims to understand how the International Centre for English Excellence (ICEE) practices the Team-of-Teams (ToT) model in the currently changing work environment. Data was gathered using in-depth interviews with eight participants of ICEE members. The result showed that ICEE practices ToT by assigning roles to each individual, and all these roles would be switched between members. The ToT model is used because it gives flexibility and help member to adapt to changes. The benefits of using the ToT model are role switching, which enables swift substitution between members, better preparation and adaptation to changes, and improvement of other skills and knowledge. The primary challenge they face is in preparing the members to take on new roles. ToT models offer flexibility and adaptability to face VUCA and are good to use, especially for a startup, small company, and organization that needs more flexibility but is not suitable for a large company that needs specialization in a certain division. Keywords: Organizational structure; Team of teams; Organization model; Pandemic